2021
DOI: 10.1021/acs.jpclett.1c00193
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Diffusion in Highly-Ordered One Dimensional Conjugated Polymers: Effects of Back-Bone Torsion, Electronic Symmetry, Phonons and Annihilation

Abstract: Many optoelectronic devices based on organic materials require rapid and long-range singlet exciton transport. Key factors controlling exciton transport include material structure, exciton–phonon coupling and electronic state symmetry. Here, we employ femtosecond transient absorption microscopy to study the influence of these parameters on exciton transport in one-dimensional conjugated polymers. We find that excitons with 2 1 A g – symmetry and a plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Based on the local phonon mode at 1097.7 cm −1 of Figure 6 , the schematic figure of the vibration of groups in the PPV chain can be drawn as Figure 7 , where the circle of pink color means the region of localized lattice distortion. Mostly, the obtained local phonon mode at 1097.7 cm −1 based on our Hamiltonian describing PPVs contributes to the formation of the exciton after annealing of the “hot” exciton, which also can be reflected by the recently observed 2 1 A g − exciton transport in one-dimensional blue conjugated polymerized polydiacetylenes without being twisted [ 22 ]. Apparently, from Figure 6 , the new localized mode possesses even parity.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Based on the local phonon mode at 1097.7 cm −1 of Figure 6 , the schematic figure of the vibration of groups in the PPV chain can be drawn as Figure 7 , where the circle of pink color means the region of localized lattice distortion. Mostly, the obtained local phonon mode at 1097.7 cm −1 based on our Hamiltonian describing PPVs contributes to the formation of the exciton after annealing of the “hot” exciton, which also can be reflected by the recently observed 2 1 A g − exciton transport in one-dimensional blue conjugated polymerized polydiacetylenes without being twisted [ 22 ]. Apparently, from Figure 6 , the new localized mode possesses even parity.…”
Section: Resultsmentioning
confidence: 60%
“…The change of electronic states then induces the self-trapping effect to act on the following photoexcitation process: the strong lattice vibration causes a local phonon mode to appear at 1097.7 cm −1 in the phonon spectrum. Additionally, this mode, based on our Hamiltonian describing PPVs, contributes to the ultimate formation of the exciton after annealing of the “hot” exciton, which also can be reflected by the recently observed 2 1 A g − exciton transport in one-dimensional blue conjugated polymerized polydiacetylenes (without being twisted) [ 22 ]. The new localized mode possesses even parity, which is an infrared phonon mode.…”
Section: Discussionmentioning
confidence: 66%
“…Instead, the efficient exciton motion at low temperatures is similar to the coherent transport of excitons. The coherent transport of singlet excitons in semiconducting polymers has been experimentally and theoretically investigated. At low temperatures, the excitonic density of states becomes narrower because the disorder induced by molecular vibration decreases, resulting in an increase in the coherent component to exciton motion.…”
Section: Temperature Dependence Of Singlet Exciton Diffusionmentioning
confidence: 99%
“…Temperature dependence measurements revealed that exciton motion is more favorable at lower temperatures as opposed to the conventional Arrhenius-type thermally activated diffusion observed in various conjugated polymer films. This thermally deactivated exciton diffusion behavior can be rationalized by taking into account the partial contribution of the coherent transport. …”
mentioning
confidence: 99%
“…This strategy is also general to other excitonic processes, where a selection rule can be made stronger by considering it in the fictitious setting. We anticipate that this approach may also be used to identify which phonon modes are important for multiexciton processes by breaking the sublattice symmetry (e.g., through intermolecular breathing modes) ,, and elucidate the role of disorder and interfacial effects to facilitate singlet fission. The proposed insight and selection rules provide a powerful computational tool and suggest a new design paradigm for experiments and for high-throughput calculations to select materials with improved efficiency and functionality for excitonic processes.…”
mentioning
confidence: 99%